Evaluation of soil quality degradation in Chinese hickory production area based on geographic information system and remote sensing technologies - WANG Luoqi; FU Weijun; YE Zhengqian; MA Shanshan; DING Lizhong; ZHAO Keli (浙江大学学报. 农业与生命科学版, 2022)
In order to comprehensively improve the soil quality of Chinese hickory (Carya cathayensis Sarg.) plantation and promote the sustainable and healthy development of hickory industry, a typical C. cathayensis plantation area (Lin’an District, Zhejiang Province) was selected for this study. Fractional vegetation cover, slope, soil fertility and soil pollution condition as evaluation indexes for soil degradation were considered. The spatial analysis of soil degradation degree for Chinese hickory plantation was carried out by fuzzy logic comprehensive evaluation method combined with geographic information system (GIS), global positioning system (GPS), and remote sensing (RS) technologies, and the corresponding management suggestions were put forward. The results showed that the soil fertility of plantation in the study area mainly belonged to the moderate degradation, and only 1.65% of the area was in a high degradation, which was centered in the north of Longgang Town and the southwest of Qingliangfeng Town. The overall soil pollution of the hickory plantation area was at a low level, only 6.35% of which was at a moderate to high degradation, mainly distributed in Daoshi and Tuankou towns. The comprehensive soil degradation of the hickory plantation mainly belonged to moderate and low degradation degrees, accounting for 66.50% of the study area. The high, moderate to high, moderate and low degradation areas accounted for 0.15%, 2.44%, 27.45% and 3.46% of the study area, respectively. The highly degraded hickory plantation was mainly distributed in the southwest of Qingliangfeng Town and the west of Longgang Town. The results will provide a theoretical basis for improving soil quality and the sustainable development of hickory property.